The role of agri-food related initiatives in sustainability transitions of agri-food systems - Elsner, Friederike; Justus Liebig University Giessen (My University, 2025)
Agri-food systems both contribute to global environmental change and are simultaneously affected by its consequences. Thereby, human activity and interactions shape desired and undesired agri-food systems’ properties. The undesired properties of current agri-food systems result in environmental, social and economic costs. Sustainability transitions of such systems are influenced by changes in social relations and deeper structural mechanisms. Individuals and groups of individuals or initiatives engage in activities, taking actions for agri-food system change. The ways these initiatives engage in change reveal systems’ malfunctions and provide insights into potential solutions and strategically relevant entry points for fostering engagement. Moreover, the ways these initiatives engage in change offer insights into tensions, goal conflicts, collaborations and resource conditions under which the initiatives operate. Existing agri-food literature on initiatives often portrays these initiatives as bottom-up driven actors within the niche. However, as agri-food system sustainability transitions are ongoing transition processes and some global or supra-national agreements to sustainable development are set in place, it is worth questioning whether all transformative activities indeed remain confined to the niche level. Drawing on transition theory, this research elaborates on the functions of agri-food related initiatives (AFIs) and the activities they perform to realise their goals as well as the influencing factors in this endeavour. Thereby, this research builds on transformative social innovation and intermediary conceptualisations and elaborates on the necessary adaptations for agri-food system analysis. The multi-level perspective on socio-technical transitions (MLP) is used to structure the analysis of the activities taking place, the functions that are being fulfilled and the influencing factors being faced. A systematic review of 58 articles on the use of MLP in agri-food system sustainability transition research paves the way for this research’ empirical investigations. The empirical analysis relies on 22 semi-structured interview transcripts conducted with 17 AFIs engaged in making their local food system more sustainable from five territorial cases in Europe (Denmark, Germany, Italy, Poland) and Northern Africa (Morocco) and on survey data of Food Policy Groups (FPGs) (n = 260), as one specific group of AFIs, across United States, middle Europe (mainly Germany) and Australia. Data is analysed using a mixed-methods approach, applying qualitative coding and statistical measures. The results show that AFIs aim to contribute to bring about change by proposing mainly agri-food related social innovations and by intermediating in the context of changing practices and social relations. Thereby, their role is influenced by drivers and barriers but not so much by their relationship to government or their type of organisation (in particular for FPGs as AFIs). A cluster is derived structuring the socially innovative activities according to social interaction processes and agri-food fields. This cluster may inspire policymakers to foster enabling environments for AFIs and support informed decision making on the types of social innovations that future agri-food systems should incorporate. The analysis of the intermediary functions shows that AFIs (here especially FPGs) intermediate between actors at the interface of civil society, science, policy and practice and assume their role through nine intermediary functions. Whether the identified niche and intermediary functions and activities are sufficient for the social innovations to diffuse remains an open question within the scope of this thesis. However, the functions and activities can be compared to those functions that the literature suggests as essential for the diffusion of technological innovation systems. Based on this comparison, the necessary functions for agri-food related social innovation systems are derived which partly deviate from the functions of technological innovation systems. Future research could take this up and develop a conceptualisation on the functions necessary for the diffusion of social innovation systems, currently lacking in the literature. The AFIs operate in interaction with other system elements, which are perceived as either enabling or constraining to their activities. The drivers AFIs face seem to be more about social relations and people whereas the barriers tend to be more of a structural or processual nature, implying that a general societal acceptance of AFIs’ activities and functions seems to be present, facilitating and justifying structural changes. The analysis of challenges suggests that support mechanisms, especially funding schemes, should be tailored to the development of social innovations and funding should not only be granted to innovation development but also to their (long-term) implementation. The results indicate that role constellations within AFIs seem to matter when it comes to the actions an AFI focuses on, which could be further pursued in future research.
Keywords: Sustainability; Transition; Agri-food-system; ddc:630